Optimisation of the continuum of supportive and palliative care for patients with breast cancer in low-income and middle-income countries: executive summary of the Breast Health Global Initiative, 2014. Issue 3 (March 2015) - Distelhorst, Sandra R; Cleary, James F; Ganz, Patricia A; Bese, Nuran; Camacho-Rodriguez, Rolando; Cardoso, Fatima; Ddungu, Henry; Gralow, Julie R; Yip, Cheng-Har; Anderson, Benjamin O; on behalf of the Breast Health Global Initiative Global Summit on Supportive Care; Quality of Life Consensus Panel Members
Summary Supportive care and palliative care are now recognised as critical components of global cancer control programmes. Many aspects of supportive and palliative care services are already available in some low-income and middle-income countries. Full integration of supportive and palliative care into breast cancer programmes requires a systematic, resource-stratified approach. The Breast Health Global Initiative convened three expert panels to develop resource allocation recommendations for supportive and palliative care programmes in low-income and middle-income countries. Each panel focused on a specific phase of breast cancer care: during treatment, after treatment with curative intent (survivorship), and after diagnosis with metastatic disease. The panel consensus statements were published in October, 2013. This Executive Summary combines the three panels' recommendations into a single comprehensive document covering breast cancer care from diagnosis through curative treatment into survivorship, and metastatic disease and end-of-life care. The recommendations cover physical symptom management, pain management, monitoring and documentation, psychosocial and spiritual aspects of care, health professional education, and patient, family, and caregiver education.